Hubungan Antara Perbandingan Sosial Dengan Kesejahteraan Subjektif Siswa SMP Pengguna Instagram - Ainayya Az Zahra; Ihsana Sabriani Borualogo (Jurnal Riset Psikologi, 2025)
Abstract. This study aims to determine the relationship between social comparison on social media, especially Instagram, and subjective well-being among junior high school students in Bandung City. Social comparison is examined based on two aspects, namely ability and opinion. The study used a quantitative correlational approach with a cross-sectional survey method and stratified cluster random sampling technique. The study involved 1,042 junior high school students in Bandung City aged 12-16 years (55% female; 45% male). Data were collected using Google Forms. Social comparison was measured using the Social Media Social Comparison (SMSC). Subjective well-being was measured using the Children's Worlds Subjective Well-Being Scale 5 items (CW-SWBS5). Data analysis used multiple linear regression to determine the relationship between variables. Descriptive statistics ANOVA was used to perform the compare means and cross-tab tests. The results showed that social comparison in the opinion aspect had a positive and significant relationship with subjective well-being (β = .140; p = < .001), while social comparison in the ability aspect showed no significant relationship (β = -.004; p = .908). This study only explained a relatively low amount of variability, namely 3.3% of the variation in subjective well-being in junior high school students. This finding suggests that social comparison is related to subjective well-being, but this relationship depends on the aspect studied.Abstrak. Penelitian ini bertujuan untuk mengetahui hubungan antara perbandingan sosial di media sosial, khususnya Instagram, dengan kesejahteraan subjektif pada siswa SMP di Kota Bandung. Perbandingan sosial dikaji berdasarkan dua aspek, yaitu kemampuan dan opini. Penelitian menggunakan pendekatan kuantitatif korelasional dengan metode cross-sectional survey dan teknik stratified cluster random sampling. Penelitian melibatkan 1,042 siswa SMP di Kota Bandung berusia 12-16 tahun (perempuan 55%; laki-laki 45%). Data diambil dengan menggunakan Google Form. Perbandingan sosial diukur menggunakan Social Media Social Comparison (SMSC). Kesejahteraan subjektif diukur menggunakan Children’s Worlds Subjective Well-Being Scale 5 items (CW-SWBS5). Analisis data menggunakan regresi linear berganda untuk mengetahui hubungan antar variabel. Statistika deskriptif ANOVA digunakan untuk melakukan uji compare means dan cross-tab. Hasil penelitian menunjukkan bahwa perbandingan sosial aspek opini memiliki hubungan positif dan signifikan terhadap kesejahteraan subjektif (β = .140; p = < .001), sedangkan perbandingan sosial aspek kemampuan tidak menunjukkan hubungan yang signifikan (β = -.004; p = .908). Hasil penelitian ini hanya mampu menjelaskan variabilitas yang relatif rendah, yakni 3.3% dari variasi kesejahteraan subjektif siswa SMP. Temuan ini menunjukkan bahwa perbandingan sosial memiliki hubungan dengan kesejahteraan subjektif, namun hubungan ini tergantung pada aspek yang dikaji.